Developing of a library operations manual for the Matayuncab Elementary School Library - Carpio, Jenivie Roman; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2019)
The Matayuncab Elementary School (MES) Library is approximately 40 sq. m. and is considered an inactive room. It has a limited collection of books; with as of December 2018, the number of books the library approximates to a 100 volumes, at most. There is a need to find donors for additional collections. In the absence of an operations manual, the researcher finds the MES Library Manual to be in need of help in assisting the personnel to operate the library properly.
This project assessed the information needs of the constituent of MES to develop a library operation manual for it. Included in which was the formulation of the MES School Library mission, vision, and objectives that was based on the vision and mission of Matayuncab Elementary School. More specially, the library operations manual aimed to address and define the managerial and technical aspects, such as, library orientations, catalogs, collection, and the like, that are needed for the library to operate.
The qualitative method was used for this project because the proponent saw it fit to conduct a survey questionnaire for students and faculty of the school to answer the current perceptions about the MES Library.
The Library Operations Manual for the Matayuncab Elementary School aims to serve as a guide to the library's daily operational services. It was created to help the library staff, students, administration, and other researchers to understand the operations of the library. This manual also aims to serve as a training tool for new staff members in operating and maintaining the library collection and services. This will serve as a ready reference for the library staff that provides specific details about the functions and procedures of the library. This library operations manual will go through a series of detailed reviews and deliberations between the administration and the library committee as regards with the changes and updates in policies and procedures of the library.
Formulation of the library operations manual and collection development plan was done at the beginning of March until the end of April 2019. Inventory, accessioning, classification and cataloguing of book and other mechanical processing of library materials will follow right after the information of the manual.
Special Problem (Master of Library and Information Science)
Keywords: Library operations -- Handbooks, manuals etc; Matayuncab Elementary School Library -- Operations manual